Non-linear dynamic analysis of coupled spar platform - Jameel, Mohammed; Ahmad, Suhail; Islam, A. B. M. Saiful; Zummat, Mohd Zamin (Journal of Civil Engineering and Management, 2013)
Spar platforms are treated as cost-effective and resourceful type of offshore structure in deep water. With increasing depth there are significant changes in its structural behaviour due to coupling of spar hull-mooring line along with radical influence of mooring line damping. So these phenomena should be precisely counted for accurate motion analysis of spar mooring system. In present study, spar platform are configured as a single fully coupled integrated model in ABAQUS/AQUA. Non-linear dynamic analysis in time domain is performed adopting Newmark-β automatic time incrementation technique. Non-linearities due to geometric, loading and boundary conditions are duly considered. Displacement and rotational responses of spar and mooring tensions are obtained during long-duration storm. spar responses get significantly modified and mean position of oscillations gets shifted after longer wave loading. The surge, heave and pitch responses are predominantly excited respectively. The energy contents of PSDs of these responses reduce considerably after long wave loading. Mooring tension responses are significantly different reflecting the damping effect of mooring lines. The pitch response is fairly sensitive to the wave loading duration. After long duration of storm the wave frequency response increases. However, low frequency and wave frequency responses may simultaneously occur due to synchronising sea states.